The modular organization of projections from areas V1 and V2 to areas V4 and TEO in macaques - Nakamura, H (J Neurosci, 1993)
In addition to the major anatomical pathways from V1 into the temporal lobe, there are other smaller, “bypass” routes that are poorly understood. To investigate the direct projection from V1 to V4 (bypassing V2) and from V2 to TEO (bypassing V4), we injected the foveal and parafoveal representations of V4 and TEO with different retrograde tracers in five hemispheres of four macaques and analyzed the distributions of labeled neurons in V1 and V2 using flattened preparations of the cortex. In V1, labeled neurons were seen after injections in V4 but not TEO. The V4-projecting neurons were located in the foveal representation of V1, in both cytochrome oxidase (CO)-rich blobs and CO-poor interblob regions. In V2, TEO-projecting neurons were intermingled with V4-projecting neurons, although the former were far sparser than the latter. Across the cases, 6–19% of the TEO-projecting neurons were double labeled, that is, also projected to area V4. Both V4- and TEO-projecting neurons formed bands that ran orthogonal to the V1/V2 border, and both were located in CO-rich thin stripes and CO-poor interstripe regions. In some cases, a continuous band of V4-projecting neurons was also found along the V1/V2 border in the foveal representation of V2. The results indicate that the pathways from V1 to V4 and from V2 to TEO involve anatomical subcompartments thought to be concerned with both color and form. These “bypass” routes may allow coarse information about color and form to arrive rapidly in the temporal lobe. The bypass route from V2 to TEO might explain the partial sparing of color and form vision that is seen after lesions of V4. By analogy, given the bypass route from the foveal representation of V1 to V4, lesions of V2 affecting the foveal visual field would also be insufficient to block color and form vision.